WAYS TO INVOLVE CHILDREN IN NEED OF SPECIAL HELP IN INCLUSIVE EDUCATION - Oppoqxo‘jayev Xojixuja Azimjon o‘g‘li; Yigitaliyeva Sarvinoz (Galaxy International Interdisciplinary Research Journal, 2023)
The issue of education of children with special needs is becoming one of the most urgent issues today. Special education has developed as an educational system for children with disabilities. This educational system is built on the assumption that the needs of children with special needs cannot be met in general education institutions. But after graduating from these special educational institutions, it becomes difficult for children with special needs to adapt and enter the social society. Again, they are forced to be far from their families and are brought up in the spirit of neglect. They may face some difficulties in self-service. In addition, many children with special needs may be left out of education.